BUSINESS ACTIVITY ONLINE (E-COMMERCE) AS A PANDEMIC ERA ALTERNATIVE - Sabilar Rosyad (EKOBIS, 2025)
At the moment, Indonesians use the internet extensively. Information technology and the internet are used in almost every activity. Therefore, it should come as no surprise that society now has a strong desire for the internet. E-commerce, or empowered businesses that rely on the internet as their main platform, have also developed as a result of this development. The process of purchasing, selling, transferring, or exchanging goods, services, or information over a computer network is known as e-commerce. E-commerce makes it easier for companies to reach customers and grow their operations. Additionally, the availability of online transactions is modernizing traditional transaction processes. Based on the phenomenon and advancements in the underlying information systems theory, this article attempts to examine and describe the different kinds of e-commerce enterprises that existed throughout the epidemic